Scope and constraints for tree planting in the irrigated landscapes of the Aral Sea Basin: case studies in Khorezm Region, Uzbekistan - Martin Worbes; Evgeniy Botman; Asia Khamzina; Alexander Tupitsa; Christopher Martius; John P.A. Lamers (University of Bonn, Center for Development Research (ZEF), 2006)
A wealth of research papers, reports, and newsprint demonstrate the wide international interest in the ecological deterioration in the Aral Sea Basin in Central Asia (CA). The demise of the Aral Sea is a symptom that results from intensive agricultural activities aiming at maximizing agricultural production while neglecting environmental sustainability, as exemplified by the land use patterns also prevalent in the Republic of Uzbekistan, one of the five newly established states in CA. The environmental degradation is acute and continues, since various factors conducive to it have not been eradicated. This discussion paper deals with the potential role of forestry-based production systems and in their contribution to counterbalancing the ecological landscape demise in the region. This discussion paper starts with a brief overview of environmental conditions in CA, followed by a discussion of forestry and agroforestry in CA's irrigated semi-arid and arid landscapes. The paper focuses on Uzbekistan, and more specifically the province (viloyat) of Khorezm, which is located at the southern rim of the Aral Sea Basin and serves as an example for the Middle Asia lowlands. The results of surveys on farmers' perception of forest and tree products, as well as the outcomes of field measurements of the productivity of tree stands and agroforestry systems, regional forestry governance, and the market situation for timber products are discussed. Following data mining of secondary sources, field, market and household surveys, combined with in-depth analyses using remote sensing techniques, the paper re-assesses the tree resources of Uzbekistan and concludes that the present use and management of trees and forests is inadequate. Well-designed multi-species windbreaks are absent (single-tree rows of mulberry comprise about 50% of the present tree strips), only 70% of the tree windbreaks were oriented in the North-South and North/West-South/East directions, from which the highest wind speeds (>3 m s-1) are generally measured, and the majority of the investigated tree strips did not satisfy the minimal height of 5 m. More than half (55%) of the strips did not stretch over the entire length of the related field. However, other structural criteria such as stand porosity and width had acceptable values. In the hedgerow systems monitored tree planting schemes varied considerably but on average were much lower compared to the recommended planting schemes by forestry administrations as the perennial crops were of more importance to the farmers. The farmers planted mostly fruit trees to increase income and improve their food basket, but none of the ca. 100 interviewed was ecologically motivated. However, the total land area of the various surveyed agroforestry systems on both private and rented land was the largest where tree age did not exceed 12 years, thus indicating the interest of tree planting. The surveys results are followed by a review of forestry policies in Uzbekistan. The paper concludes with a set of recommendations concerning managerial and research needs for forest and agroforestry systems in irrigated drylands of CA, and outlines the opportunities and need for external support at both the country and sub-regional level. Despite the role trees could potentially play, the lack of training of the farming population, reduced capacities of the forestry administration and their staff as well as shortcomings in the forest legislation have resulted in many underperforming "goodwill" efforts. Due to the complexity of the social, economical and physical components and their interdependencies, this paper calls for integrated knowledge generation, concerted action and for administrative and research support. The crisis in the Aral Sea Basin has a strong global dimension, which calls for targeted support at both country and international donor community levels.
Keywords: 330; Agroforstwirtschaft; Bewässerungslandwirtschaft; Usbekistan; Aralsee